2016
DOI: 10.1017/s0007114516001963
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of legumes on parameters of the metabolic syndrome: a systematic review of trials in animal models

Abstract: Legume consumption plays a pivotal role in the prevention and treatment of the metabolic syndrome (MetS). This systematic review aimed to highlight the beneficial effects of legume interventions for the prevention and/or improvement of parameters related to the MetS and the implicated metabolic pathways so far reported. The methodology involved a search in four electronic databases (Medline, Web of Science, Scopus, Cochrane Library) from January 2007 to December 2014, considering as descriptors 'Metabolic Synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…The pattern salty snacks & sauces, for example, are characterised by "unhealthy" food groups that have a high sodium load, such as salty snacks and sauces. However, this pattern is also characterised by food groups that can exert specific beneficial effects on metabolic health, such as nuts and legumes [51]. Indeed, we have previously shown that specific food items, such as coffee and tea, are associated with NAFLD independent of dietary quality [52].…”
Section: Discussionmentioning
confidence: 97%
“…The pattern salty snacks & sauces, for example, are characterised by "unhealthy" food groups that have a high sodium load, such as salty snacks and sauces. However, this pattern is also characterised by food groups that can exert specific beneficial effects on metabolic health, such as nuts and legumes [51]. Indeed, we have previously shown that specific food items, such as coffee and tea, are associated with NAFLD independent of dietary quality [52].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to their nutritional value, the specific structure of their nutrients, and the presence of several bioactive components usually grouped under the generic description of non-nutritional compounds, provide legumes with beneficial properties for the management of several pathologies, and confer them great value as functional foods [2]. In particular, legumes can exert significant protection against metabolic syndrome components such as high blood pressure, hyperlipidaemia, insulin resistance and diabetes [3], as well as several types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinemia and hyperglycemia induce oxidative stress (which damages arterial walls) [48], reduces nitric oxide (which is a powerful vasodilator and helps reduce inflammation) [24] and finally leads to arterial wall damage and arterial stiffness [13], meaning that low-glycemic index pulse-based foods have the potential to prevent arterial stiffening, a major risk factor for cardiovascular disease [49]. Pulses might further reduce harmful blood lipid levels by up-regulating genes involved in acetyl-CoA degradation and β-oxidation, and down-regulating genes related to lipogenesis and glycolysis [50]. In the current study, the reduced diastolic blood pressure on the pulse diet might be due to the lower sodium content of this diet.…”
Section: Discussionmentioning
confidence: 99%